1977
DOI: 10.1128/jb.130.1.297-302.1977
|View full text |Cite
|
Sign up to set email alerts
|

Localization of enzymes in Ureaplasma urealyticum (T-strain mycoplasma)

Abstract: Ureaplasma urealyticum cells were lysed by osmotic shock or by digitonin. The membrane fraction contained four to ten times as much protein as the cytoplasmic fraction. These values are in large excess of those reported for classical mycoplasmas, suggesting that the Ureaplasma membrane fraction was heavily contaminated with proteins derived from the growth medium. The U. urealyticum urease activity was localized in the cytoplasmic fraction, whereas the adenosine triphosphatase activity was localized in the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…Jeffries (90,91) demonstrated that urease activity in 22 species of bacteria was associated with soluble extracts of the cells, which were ruptured by sonication or French pressure cell lysis. In cell fractionation studies of K. aerogenes (59), U. urea'lticiun (44,145,189,236), Providencia stiuar-tii (158), and Protelus lirilbilis (98), the majority of urease partitioned with the soluble cytoplasmic fraction. Analysis for control enzymes, known to reside in specific cell fractions, supported the conclusion that urease is cytoplasmic in these species.…”
Section: Cellular Localization Of Ureasementioning
confidence: 99%
See 2 more Smart Citations
“…Jeffries (90,91) demonstrated that urease activity in 22 species of bacteria was associated with soluble extracts of the cells, which were ruptured by sonication or French pressure cell lysis. In cell fractionation studies of K. aerogenes (59), U. urea'lticiun (44,145,189,236), Providencia stiuar-tii (158), and Protelus lirilbilis (98), the majority of urease partitioned with the soluble cytoplasmic fraction. Analysis for control enzymes, known to reside in specific cell fractions, supported the conclusion that urease is cytoplasmic in these species.…”
Section: Cellular Localization Of Ureasementioning
confidence: 99%
“…Therefore, in this organism neither product of urea hydrolysis was used at significant levels by the cell. Masover et al (145) reasoned that ammonia generated by urease would be protonated at physiological pH, resulting in ammonium ion (NH4') formation. This T \N NH4 NH3 FIG.…”
Section: Ureaplasma Energy Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…U. ureaiyticum urease is localized in the cytoplasm of the celt (Masover et aL, 1977;Vinthier, 1976) and was shown to exhibit a specific activity greater than that of crystalline jack bean urease (Blanchard ef a/., 1988;Stemke et al, 1987). Three structural subunits of the purified enzyme were characterized as 72 kD, 14kD and 11 kD polypeptides (Thirkell etal.. 1989).…”
Section: Introductionmentioning
confidence: 99%
“…lost from cells as they age and lyse. It has been suggested that urease is cytosohc [6,12,13]. Sections probed with UU8/17 and pro-…”
Section: Localisation Of Ureasementioning
confidence: 99%